The Influence Of Ease Of Use, Trust And Safety On The Go-Food Application To The Millenias Of Makassar City : Application Of Acceptance Model Theory - Ferdinandus Sampe (Institute of Computer Science (IOCS), 2022)
This study aims to determine whether the factors of convenience, trust, and security significantly affect the interest in using the Go-Food application for millennials in Makassar City. Sampling in this study uses the purposive sampling technique. Data were collected using a set questionnaire. A total of 96 respondents were successfully invited to participate and fill out the questionnaire. Data were analyzed descriptively and regression analysis to test the research hypothesis. The test of this research was conducted using the SPSS version 22 program. The results showed that the security and usability variables significantly affected the interest in using the Go-Food application. While the ease of use variable has no significant effect on the interest in using the Go-Food application.